UPAYA PENURUNAN KEKERUHAN DAN WARNA AIR SUMUR GALI MENGGUNAKAN KOAGULAN BIJI KELOR DAN FILTRASI KARBON AKTIF - Sulaiman Hamzani (Purifikasi, 2012)
Digging well water which is used in the Housing residents Pulo Gebang, East Jakarta is not qualified as drinking water and clean water, the water looks dirty and reddish brown. Based on a preliminary survey of wells, it is not eligible construction and quality. Laboratory results showed turbidity 29 NTU and color 300 TCU. According to the Minister Regulation. 492/Menkes/Per/IV/2010 about drinking water quality requirements 5 NTU turbidity and color of 15 TCU. This study aims to determine the optimum dose of coagulant Moringa seed and produce active carbon filtration thickness decreased turbidity and color levels to meet drinking water quality standard requirements. Research methodology is jartest test coagulant dose variation moringa seeds with 10-80 mg/L, then the optimum dose used in the process of coagulation-flocculation and filtration with granular activated carbon variations in the thickness of 10-100 cm in diameter filter tube 4 ". Turbidity levels measured by turbidimeter and colors with a colorimeter. The results obtained after treatment for 2 NTU turbidity level (95.6% reduction efficiency) and color 10 TCU (88.9% removal efficiency). This treatment combination is able to meet the requirements of drinking water quality with optimum dose of coagulant Moringa seeds 60 mg / L and an active carbon filter with a thickness of 100 cm